Biometry of female genitalia of Murrah buffalo (Bubalus bubalis) - KUMAR, S; AHMED, F A; BHADWAL, M S (The Indian Journal of Animal Reproduction, 2023)
Biometrical study of buffalo revealed the mean length, breadth and thickness of the left ovary to be 2.35±0.08, 1.90±0.05and 1.54±0.06 cm and that of the right ovary as 2.13±0.08, 1.68±0.08 and 1.43±0.04 cm, respectively . The average length andbreadth of the left oviduct was 23.28±0.58 and 0.20±0.00 cm, and that of the right oviduct was 23.10±0.05 and 0.20±0.06 cm,respectively. Length, breadth and thickness of the left uterine honr was 39.25± 1.73, 1.78±0.06 and 0.84±0.05 cm and that for theright horn was 38.65±1.41, 1.69±0.07 and 0.84±0.04 cm, respectively. Length, breadth and thickness of the corpus luteum measured5.28±0. I 9, 1.89±0.09 and 1.10±0.05 cm, respe"cti vely and that for the cervix was 6.11±0.30, 1.93±0.07 and 1.46±0.07 cm,respectively. In case of paired organs the dimensions of the left side were found to be slightly higher than the right side.
Keywords: Biometry; female genitalia; Murrah buffalo